MECHANISM FOR IMPLEMENTING SOLAR PANELS IN MULTI-STORY HOUSES AND ITS EFFICIENCY - Boboqulov, Sanjar Bakhronkulovich (THE INNOVATION ECONOMY, 2026)
This article is dedicated to achieving electricity stability, optimizing utility costs, and justifying economic efficiency by implementing solar panels on the roofs of multi-story buildings to increase electricity supply in the Samarkand region. Additionally, the article develops a mechanism based on the positive and negative aspects of solar panel implementation and presents proposals and recommendations for its development.